Fostering Teacher Performance through Creativity and Innovative Work Behavior: A Meta-Analysis - Setiawati, Luhur; Lapasau, Merry; Widodo, Widodo; Musliman, Acep; Nurjanah, Nurjanah (Kuras Institute, 2025)
Teachers’ performance plays a crucial role in achieving educational quality, and two important factors that can enhance it are creativity and innovative work behavior (IWB). This study aims to examine the influence of these two variables on teachers’ performance through a meta-analysis approach. A total of 25 effect sizes from scientific articles published between 2020 and 2025 were analyzed using JASP software version 0.19.3.0, with two independent variables, creativity and IWB. The results indicate that creativity has a significant positive effect on teachers’ IWB with an effect size of 0.561 (SE = 0.133; p = 0.001) and a heterogeneity [(Q = 542.751; p < 0.001; τ² or τ > 0; I² (%)]. Similarly, IWB also shows a significant effect with an effect size of 0.389 (SE = 0.046; p < .001) and a heterogeneity [Q = 66.886; p < 0.001; τ² or τ > 0; I² (%)]. These findings demonstrate that creativity and IWB consistently improve teachers’ performance. Therefore, enhancing teachers’ creativity and IWB should be integral to continuous professional development programs in educational institutions.